Implementasi Strategi Manajemen Konflik untuk Mencegah Kekerasan di Sekolah - Zohriah, Anis; Torismayanti, Torismayanti; Firdaos, Rijal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to provide an understanding of the implementation of conflict management strategies to prevent violence in schools. The research method used is a literature study. The literature study approach requires a number of reading materials to be carried out by managing research materials, taking notes while reading, and gathering information from the library. This study found several things about the correlation between conflict and violence that occurred in the school environment. Conflicts that arise in schools can be reduced and even overcome by using conflict management techniques to the maximum extent possible. In addition, this study discusses effective conflict management in schools which is important for preventing violence. This involves taking proactive and reactive actions to resolve conflicts before they lead to violence. It also involves education and training for students, teachers and staff to resolve conflicts peacefully. Good conflict management can help create a safe and conducive school environment for learning. Therefore, good conflict management in schools is very important to prevent violence and ensure student safety. Keywords: Conflict, Conflict Managemen, Violence in Schools